A Situation, a Narrative, and a Life History. The Case of Natalia - Riemann, Gerhard (Qualitative Sociology Review, 2014)
I will first focus on problems which might emerge in narrative interviews with people who have experienced long-term trajectories of suffering, before discussing the researcher’s specific style of doing this particular biographical interview – a style which is marked by sensibility and considerateness, but might contain some problems nevertheless. Afterwards, I will deal with two formal features of the interviewee’s introductory narrative – a complicated background construction and an extended pre-coda commentary – in order to reveal the analytical significance of these features for a deeper understanding of the interviewee’s life history and her way of making sense of her experiences. The article ends with a discussion of some topics which are relevant for an analytical abstraction.